Identification of a novel HLA‐DPB1, HLA‐DPB1*687:01, in an Italian renal transplant candidate. (10th April 2019) - Biagini, Chiara; Fornaciari, Silvia; Mariotti, Maria L.; Mazzoni, Alessandro; Curcio, Michele
Abstract: Two adjacent nucleotide substitutions in exon 2 characterize the novel class II HLA‐DPB1*687:01 allele.